Mechanical properties of epoxy nanocomposites using titanium dioxide as reinforcement – A review. (1st October 2015) - Pinto, Deesy; Bernardo, Luís; Amaro, Ana; Lopes, Sérgio
Highlights: EP are brittle and show poor resistance to crack initiation and crack propagation. TiO2 nanoparticles with or without SM can be used as fillers to reinforce EP. Reinforced EP nanocomposites exhibit improved properties with low filler contents. Experimental results from previous studies are presented, compared and discussed. Future directions for the development of these TiO2 nanocomposites are presented. Abstract: Epoxy (EP) resins have been widely used and thus subjected to extensive investigations over the past few decades. It is well known that EP resins are brittle and show poor resistance to crack initiation and crack propagation. For these reasons, in recent years, research activities have been focused on techniques to improve the fracture resistance (toughness and brittleness) of EP resins. One of the most studied techniques consists to incorporate inorganic nanoparticles into the polymer matrix, such as titanium dioxide (TiO2 ), alumina (Al2 O3 ), silica (SiO2 ), carbon black, nanoclays, carbon nanotubes (CNTs) and others. The resulting nanocomposites can exhibit improved thermal, mechanical (including toughness), rheological, electrical and optical properties, among others, even with very low nanofiller contents. These nanocomposites constitute an alternative product to metal-based ones and shows great potential as multifunctional materials for a wide variety of applications, such as civil construction, automotive, aerospace, optoelectronic devices, semiconductor devices and others. In this paper, an attempt is made to review and highlight some recent findings and also some trends to show future directions and opportunities for the development of polymer nanocomposites reinforced with TiO2 nanoparticles. Several experimental results from previous studies on the mechanical properties of such polymer nanocomposites are presented, compared and discussed. It is shown that the addition of TiO2 nanoparticles into EP resin can improve important mechanical properties, namely tensile modulus, tensile strength, toughness and fracture toughness, fracture energy, flexural modulus, flexural strength, elongation at break, fatigue crack propagation resistance, abrasion, pull-off strength and fracture surface properties, even at low filler contents.